Efektivitas Pupuk Hayati Bactoplus dalam Meningkatkan Efisiensi Pemupukan NPK pada Tanaman Kentang (Solanum tuberosum L.) Varietas Chitra: Effectiveness of Bactoplus Biofertilizer in Increasing the Efficiency of NPK Fertilizer on Potato Plant (Solanum tuberosum L.) Chitra Variety - Nurhidayati Nurhidayati; Aluh Nikmatullah; Hery Haryanto (LPPM Universitas Mataram, 2023)
This study was undertaken to examine the effectiveness of Bactoplus biofertilizer in increasing the efficiency of NPK fertilization on potato of Chitra variety. The experiment used a two-factor factorial randomized block design, namely: doses of NPK fertilizer (N1= 650 kg ha-1 /100% of the recommendation; N2= 487.5 kg ha-1/75% of the recommendation; and N3= 325 kg ha-1/50% of the recommendation) and Bactoplus biofertilizer (H0 = without Bactoplus biofertilizer and H1 = with Bactoplus biofertilizer). The results showed that the biofertilizer Bactoplus was effective in increasing the efficiency of NPK fertilizer, particularly to plant height at 3 weeks after planting (MST) and number of leaves at 7 MST. At the same dosages of NPK fertilizer, application of biofertilizer increased the plant height at 3 MST and the number of leaves at 7 MST, The best growth was achieved when the plants was treated with 75% of NPK in combination with Bactoplus application. The effect of each factor showed that application of Bactoplus biofertilizer increased growth, yield and quality of potato tubers. In adition, the dose of NPK fertilizer affected the growth of potato plants but did not affect the yield and quality of potato tubers.